2006
DOI: 10.1212/01.wnl.0000238508.68593.1d
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists and cardiac valvulopathy in Parkinson disease

Abstract: The frequency of valvulopathy was significantly increased in the cabergoline group. Our results indicate that high cumulative dose and long-term treatment with cabergoline are risk factors for valvulopathy in patients with Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 20 publications
5
61
3
3
Order By: Relevance
“…In our study, despite the similarity of mean daily doses of cabergoline, duration of therapy and therefore cumulative dose was higher compared to other studies (15). Moreover composite regurgitation score was higher in patients using cabergoline which was associated both with duration and cumulative dose of cabergoline therapy as in line with previous studies (15,18). In addition to valvular regurgitation, morphologic features including leaflet and subvalvular apparatus thickening were more prevalent in patient using cabergoline similar to previous studies (19).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, despite the similarity of mean daily doses of cabergoline, duration of therapy and therefore cumulative dose was higher compared to other studies (15). Moreover composite regurgitation score was higher in patients using cabergoline which was associated both with duration and cumulative dose of cabergoline therapy as in line with previous studies (15,18). In addition to valvular regurgitation, morphologic features including leaflet and subvalvular apparatus thickening were more prevalent in patient using cabergoline similar to previous studies (19).…”
Section: Discussionsupporting
confidence: 84%
“…Several cross-sectional studies have demonstrated a significantly increased risk of valvular fibrosis in Parkinson's patients treated with the ergot-derived dopamine agonists (DAs) pergolide and cabergoline (1,2,3,4,5,6). Extensive research over the last decade has highlighted the crucial role of 5-hydroxytryptamine 2B receptors (HTR2B) in the pathogenesis of this fibrotic valvular heart disease (FVHD) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term treatment of Parkinson's disease with the dopamine agonists (DAs) pergolide and cabergoline has been established to be associated with a significantly increased risk of developing fibrotic valvular heart disease (FVHD) (1,2,3,4). The process is triggered by the activation of the serotonin receptors (5HT 2b ), which are highly expressed in cardiac valves (5,6,7).…”
Section: Introductionmentioning
confidence: 99%